E-Learning Development Management with The Schoology Improving Geographic Learning Literation - Sahudra, Tengku Muhammad; Taher, Alamsyah; Kemal, Isthifa (Universitas Pendidikan Ganesha, 2021)
Lack of development of instructional media reduces student interest in learning so that it affects student literacy in the learning process. The purpose of this research is to develop E-learning with schoology to improve literacy in geography learning in flora and fauna material. This type of research is development research. The data collection technique was carried out through three data collection methods, namely observation, questionnaires and tests. The data analysis technique used in this research is quantitative data analysis techniques. The results of this study are experts in the validation of E-learning product designs with schoology which consists of three components of the validator's most dominant assessment, namely the element of product quality with a value of one validator of 52%, and two components of the validator's assessment. 78%, and the results of product trials with a value of 0.42. %. So it can be concluded that E-learning with schoology is declared suitable for use in the learning process and is very easy to use based on literacy in geography learning.